State Variation in Low-Dose Computed Tomography Scanning for Lung Cancer Screening in the United States. (12th November 2020) - Fedewa, Stacey A; Kazerooni, Ella A; Studts, Jamie L; Smith, Robert A; Bandi, Priti; Sauer, Ann Goding; Cotter, Megan; Sineshaw, Helmneh M; Jemal, Ahmedin; Silvestri, Gerard A
Abstract: Background: Annual lung cancer screening (LCS) with low-dose chest computed tomography in older current and former smokers (ie, eligible adults) has been recommended since 2013. Uptake has been slow and variable across the United States. We estimated the LCS rate and growth at the national and state level between 2016 and 2018. Methods: The American College of Radiology's Lung Cancer Screening Registry was used to capture screening events. Population-based surveys, the US Census, and cancer registry data were used to estimate the number of eligible adults and lung cancer mortality (ie, burden). Lung cancer screening rates (SRs) in eligible adults and screening rate ratios with 95% confidence intervals (CI) were used to measure changes by state and year. Results: Nationally, the SR was steady between 2016 (3.3%, 95% CI = 3.3% to 3.7%) and 2017 (3.4%, 95% CI = 3.4% to 3.9%), increasing to 5.0% (95% CI = 5.0% to 5.7%) in 2018 (2018 vs 2016 SR ratio = 1.52, 95% CI = 1.51 to 1.62). In 2018, several southern states with a high lung-cancer burden (eg, Mississippi, West Virginia, and Arkansas) had relatively low SRs (<4%) among eligible adults, whereas several northeastern states with lower lung cancer burden (eg, Massachusetts, Vermont, and New Hampshire) had the highest SRs (12.8%-15.2%). The exception was Kentucky, which had the nation's highest lung cancer mortality rate and one of the highest SRs (13.7%). Conclusions: Fewer than 1 in 20 eligible adults received LCS nationally, and uptake varied widely across states. LCS rates were not aligned with lung cancer burden across states, except for Kentucky, which has supported comprehensive efforts to implement LCS.